Lived Experiences among Rice Farmers on Tare Weight Deduction in Lapinig, Kapatagan, Lanao Del Norte - Esparcia, Arnel A.; Undona, Zanlin; Laranjo, Rubie Jane L.; Solatorio, Shalley Mae D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This phenomenological qualitative study explored the lived experiences of 14 rice farmers in Lapinig, Kapatagan, Lanao del Norte, aiming to investigate the challenges and financial impact of unregulated 'Tarha' (tare weight deduction) practices on their livelihood.  Using a phenomenological approach under qualitative research design and purposive sampling method, data were collected through in-depth interviews with 14 rice farmers. The data gathering was conducted over two (2) days.  Thematic analysis revealed three key themes: (1) Excessive Tare Deduction as a Major Challenge, where farmers shared how large deductions significantly reduced their profit; (2) Coping Mechanisms through Sun-Drying and Palisan, reflecting how farmers reduce moisture and impurities to lower deductions; and (3) Calls for Reduction of Tare Deduction, where participants voiced the need for fairer and standardized deduction practices. Findings indicate that unregulated "Tarha" practices negatively affect the financial sustainability of farmers. The study recommends stricter monitoring by the Department of Agriculture, transparent guidelines from traders, and empowerment programs for farmers to promote fair trade and agricultural sustainability.